Human Umbilical Cord Mesenchymal Stem-Cell Therapy to Increase the Density of Osteoporotic Mandibular Bone - Hendrijantini, Nike; Hartono, Poedjo; Ari, Muhammad Dimas Aditya; Rantan, Fedik Abdul (European Journal of Dentistry, 2019)
Objective The aim of this study is to evaluate the feasibility of human umbilical cord mesenchymal stem-cell (hUCMSC) therapy in increasing osteoporotic mandibular bone density in a rat model by determining changes in alkaline phosphatase (ALP), osteocalcin, type 1 collagen, and trabecular bone area after treatment.Materials and Methods This research adopted an experimental posttest-only control group design. Thirty female Wistar rats were randomly divided into six groups, namely, a control group with rats postsham surgery (T1), osteoporotic model postovariectomy rats (T2), postovariectomy rats 4 weeks after gelatin injection (T3), postovariectomy rats 8 weeks after gelatin injection (T4), postovariectomy rats 4 weeks after hUCMSC injection (T5), and postovariectomy rats 8 weeks after hUCMSC injection (T6). The rats were all sacrificed for histological and immunohistochemical examinations of ALP, osteocalcin, type 1 collagen, and trabecular bone area.Results Increased expression of ALP, type 1 collagen, and osteocalcin, as well as increased trabecular bone area, was observed in the treatment groups compared with that in the osteoporotic groups.Conclusion hUCMSCs produce significant osteogenic effects and increase osteoporotic mandibular bone density in the animal model. Increases in bone density are demonstrated by the higher levels of ALP, osteocalcin, and type 1 collagen, as well as increases in the trabecular bone area.
Keywords: human; mandibular; osteoporosis